Foreign direct investment and employment in transition economies - Saul Estrin (IZA World of Labor, 2017)
Foreign direct investment (FDI) has been argued to improve company performance and stimulate growth and employment. Transition economies of Central and Eastern Europe (CEE) faced a desperate need to join the global economy, to improve their competitiveness and to create jobs through FDI. So, did the FDI come, and did it deliver what was expected? FDI levels were high for CEE, and for some resource-rich transition countries (e.g. Russia and some of Central Asia), but primarily delivered significant benefits (e.g. employment) for the former. FDI arrived much later to other transition countries (e.g. the former Soviet republics and the Balkans) and had much less impact.
Keywords: J6; P2; O4; F2; 330; foreign direct investment; transition countries; unemployment